Improving the sinter productivity with increased specular iron ore in sinter blend - Kumar S.; Jaiswal A.; Sah R. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2022)
Specular iron ores are medium grade iron ores suitable for the use in agglomeration process. However, due to their hard texture, undesirable particle size and shape, poor assimilation performance and low reactivity at high temperature, its uses in agglomeration is very limited and restricted to almost 3-10% at most of the plants. In the present study, the effect of specular iron ore on sintering performance and sinter qualities are examined. It was observed that an increased proportion of specular iron ore in sinter blend showed poor sintering performance in both laboratory scale studies and plant scale trials. In the present work, the effect of blending of specular iron ore with goethite iron ore in sinter mix on sintering performance was examined and an optimum iron ore blend ratio for sustainable performance and quality was proposed. To increase the specular iron ore usage in sintering, goethitic iron ore up to 30% was introduced in sinter blend to overcome the deteriorating nature of specular iron ore. The goethite iron ore contains chemically bonded water which gets removed at higher temperatures (300-500°C) during sintering. The evaporated water gets cooled at lower bed and condenses which retards the air flow during sintering process and thus the combustion zone stays for longer time allowing better melt assimilation and sinter qualities. The poor melt assimilation of specularite is thus countered in presence of goethite iron ore. Having better reactive and hydrophilic nature of goethite iron ore, nullifying or reducing the ill effect of poor reactive and hydrophobic characteristics of specular iron ore during granulation and sintering process. Therefore, the blended specular and goethite iron ore resulted in improved sintering rate and consequently improved sinter productivity. The present work proposed usage of up to 30% of specular iron ore when blended with goethite iron ore in sinter making.